P185 Primary cardiac lymphoma: an unexpected finding. (17th January 2020) - Riesgo, A; Ibero, J; Rodriguez, M; De La Torre, F; Muniz, J; De La Fuente, A; Salterain, N; Diaz, I; Rifon, J J; Bastarrika, G; Gavira, J J
Abstract: BACKGROUND: Primary cardiac malignancies are rare, with a reported incidence of 0.1%. Up to 10% of cardiac tumors are malignant and primary cardiac lymphoma represents (PCL) a very low proportion of them. The wide variety of clinical manifestations and the inespecificity of them, difficults the diagnosis and delays treatment impacting directly in the prognosis of these patients. Here we present a lady with diagnosis of PCL treated in our center. CASE REPORT: We present a 69 year old female with arterial hypertension and paroxismal atrial fibrilation that attended our clinic in april 2013. She referred severe dyspnoea with daily activities and peripheral oedema for the last three weeks. She also complaint of painful swallowing for bothliquids and solids. Physical exploration was unremarkable and observations where within normal limits. Transthoracic echocardiogram (TTE) was performed which showed an hipoechogenic mass invading the right ventricle, both atria and left ventricle outflow tract. She underwent cardiac MRI which revealed a myocardial isointense mass, with marked signal enhancement in T2 and heterogeneity in late gadolinium enhancement sequences, that was consistent with primary cardiac lymphoma. For histologycal characterization, biopsy of the mass guided with endoscopic ultrasonography was performed, confirming B-cell lymphoma. Positron emmision tomography (PET) scan showed bulky hypercaptant mass invading both atria, superior vena cava and pericardium, with hypercaptant adenopathies in right pulmonary hilum, subcarinal and phrenic chain. Her case was discussed in multidisciplinary team meeting and prompt initiation of treatment under R-CHOP regime was decided. After three cycles, follow up PET was requested, and revealed complete metabolic response. A repeat TTE showed only minimal infiltration of the right atria without ventricular involvement or hemodynamic compromise. DISCUSSION: The patient we presented, was sent to Cardiology due to heart failure symptoms. Acute heart failure as well as embolisation and life-threatening arrythmias are typical manifestations of PCL. As reported in the literature, our case was a diffuse large B-cell lymphoma, which is the most frequent subtype. Dysphagia, exertional dyspnoea and constitutional symptoms can be present in early stages, as our patient referred. The main strength of this case is based on the quick diagnosis and early treatment. In contrary to what is reported, the overall survival was excellent, and to date the patient is still alive with no signs of relapse. Although TTE sensitivity is 55-60%, it has a key role in the diagnosis, which was supported later on MRI. Right chambers (specially right atria) are more typically involved than the left heart, including right venous drainage. Early systemic chemotherapy can achieve a high response rate and improve survival.